Analisis Kadar Total Fenolik Ekstrak Etanol Daun Ciplukan (Physalis angulata L.) Dengan Metode Partisi Bertingkat Di Kawasan Geothermal Dan Non-Geothermal - Mahmudi Mahmudi; Saiful Azhari; Aida Apriani; Rinaldi Rinaldi; Rozatun Uliani (Journal of Pharmaceutical and Sciences, 2026)
Ciplukan (Physalis angulata L.) is a tropical plant with numerous benefits and is cultivated as a raw material for biopharmaceuticals, so it is no longer known as a lying plant or a weed in vacant lots by the public. Ciplukan contains secondary metabolites that can be used as active ingredients in drugs with antihyperglycemic, anti-inflammatory, antidiabetic, and cytotoxic activities. Phenolic compounds are secondary metabolites found in almost all parts of the plant. Phenolic compounds also have antioxidant properties. This is because phenolic compounds can react with free radicals and eliminate their activity so that they are no longer harmful to human cells. This study aims to determine the total phenolic content in ethanol extracts of ciplukan (Physalis angulata L.) leaves in geothermal and non-geothermal areas using a multilevel partition method. The data used to obtain total phenolic content was calculated based on a calibration curve from the readings from a UV-Vis spectrophotometer. Total phenols were calculated using a linear regression equation from the gallic acid calibration curve. Data obtained from the laboratory were processed manually and analyzed descriptively in the form of tables and graphs. The results of the total phenolic content test of the ethanol extract of ciplukan leaves (Physalis angulata L.) for the ethyl acetate fraction of the geothermal area obtained a phenolic content of 150.88% and for the ethyl acetate fraction of the non-geothermal area obtained a phenolic content of 131.68%. The results of the total phenolic content test of the ethanol extract of ciplukan leaves (Physalis angulata L.) for the N-Hexane fraction of the geothermal area obtained a phenolic content of 125.72%, and the results for the N-Hexane fraction of the non-geothermal area obtained a phenolic content of 75.01%. These results indicate that the phenolic content of ethanol extracts of ground cherry (Physalis angulata L.) leaves in geothermal areas contains higher total phenol levels than those in non-geothermal areas. These results can also serve as a basis for developing standards for ciplukan extracts from geothermal sources as a source of natural antioxidants.